EVALUASI PELAKSANAAN PROGRAM GERDU KEMPLING DI KECAMATAN SEMARANG BARAT - Rudi Santoso A; Ahmad Taufiq; Supratiwi . (Journal of Politic and Government Studies, 2013)
Abstract-In efforts to achieve the vision ofSemarang City as the trade and cultural services tothe public welfare, the government implementSapta program, one of which is Gerdu Kemplingprogram (Integrated Movement in Alleviation ofPoverty in Health, Economy, Education,Infrastructure, and Environment Sectors), aprogram that focuses on the areas of povertyreduction. Although it has been carefully designed,but nature doing so, the program still encountersmany obstacles and shortcomings. An example is inthe District of West Semarang. In 2007 WestSemarang district representing as the urbanpoverty since the West Semarang district has themost impoverished families among existingdistricts. However, the people in this region inaverage did not know very well about the programand the program is less known by the public atlarge, whereas they are the main target of theprogram that was launched in March 2011. Thisstudy aims to determine the implementation of theGerdu Kempling program in the District of WestSemarang as well as to determine the supportingand inhibiting factors in the implementation of theprogram.This study is an evaluative research, whichundergo assessment studies for the implementationof government policy, particularly on the GerduKempling program in West Semarang District inaccordance with the goals, objectives, and theimpact of items desired by using a qualitativeapproach. Sources of data are primary data thatdirectly obtained through field observations andinterviews with the Local Government (LG) ofSemarang and West Semarang District. After thedata reduction, the results of evaluative researchwill be presented analytically.The results showed: 1) Kempling GerduProgram still not fully known and understood bythe public as an object of policy, it is caused by thelack of systematic program, less the maximumgovernment in fostering citizens to develop theirbusiness, especially in the capital for the businesscommunity; 2) The supporting factors that supportthe implementation of programs is Gerdu Kemplingprogram are good coordination and synergybetween Semarang City Government bureaucratswith stakeholders, the funding and businessfacilities of the CSR program of the business world(banks, state / local enterprises and private), aswell as quite effective guidance on education andtraining of Semarang City Government to theprogram implementers. While the inhibiting factorsare: the lack of response from the community ofinmates, the lack of understanding to the GerduKempling program, the limited funding andfacilities budget of Semarang City Government aswell as from the stakeholders and the lack ofsocialization of the program in Semarang cityresidents.Keywords: Sapta program, Poverty AlleviationProgram, the City of Semarang, Gerdu Kempling